Spatial and Temporal Variability of Soil CO2 Flux in Sugarcane Green Harvest Systems - Moraes Tavares, Rose Luiza; Souza, Zigomar Menezes de; La Scala, Newton [UNESP]; Ferreira Castioni, Guilherme Adalberto [UNESP]; Souza, Gustavo Soares de; Rodrigues Torres, Jose Luiz (Soc Brasileira De Ciencia Do Solo, 2016)
The sugarcane green harvest system, characterized by mechanized harvesting and the absence of crop burning, affects soil quality by increasing crop residue on the soil surface after harvest; thus, it contributes to improving the physical, chemical, and microbiological properties and influences the soil carbon content and CO2 flux (FCO2). This study aimed to evaluate the spatial and temporal variability of soil FCO2 in sugarcane green harvest systems. The experiment was conducted in two areas of sugarcane in Sao Paulo, Brazil: the first had a 5-year history of sugarcane green harvest (SG-5) and the second had a longer history of 10 years (SG-10). The temporal FCO2 were evaluated in the dry and rainy periods, and spatial variability in the dry period, and related to soil chemical and physical properties, including organic C porosity, bulk density, soil penetration resistance, mean weight diameter of soil aggregates, clay, P, S, Ca, Mg and Fe. The temporal variability indicated no differences between the dry and rainy periods in SG-10, while in SG-5 soil moisture was increased by 33 % in the rainy period. The spatial variability indicated a different pattern from the temporal one, where FCO2 in SG-10 was correlated with soil temperature, air-filled pore space, total porosity, soil moisture, and the Ca and Mg contents; in the SG-5 area, FCO2 was correlated with soil mean weight diameter of soil aggregates and the sulfur content.
Keywords: CO2 emission; soil respiration; straw; mechanized harvest; physical properties